Extracellular microvesicles from patients with Rheumatoid arthritis promote dendritic cell activation in vitro - Buttari, Brigitta; Recalchi, Serena; Riitano, Gloria; Capozzi, Antonella; Ucci, Federica Maria; Manganelli, Valeria; Fratini, Federica; Profumo, Elisabetta; Garofalo, Tina; Alessandri, Cristiano; Misasi, Roberta; Conti, Fabrizio; et al. (Frontiers in Immunology, 2025)
IntroductionRheumatoid Arthritis (RA) is a systemic autoimmune disease characterized by chronic synovial inflammation affecting diarthrodial joints, with cartilage destruction and bone erosion. Environmental inflammatory stimuli can induce maturation of dendritic cells (DCs), which promote differentiation and activation of effector T lymphocytes. We previously highlighted the role of extracellular microvesicles (EMVs) in pathogenesis by carrying antigens that trigger autoantibody production. In this investigation we verified whether EMVs may activate immature monocyte-derived DCs, inducing phenotypic and functional characteristics of mature DCs.MethodsEMVs were obtained from 7 RA patients naïve to biological disease-modifying anti-rheumatic drugs (DMARDs) and tested for their capability to activate DCs from healthy donors.ResultsWe preliminary confirmed by western blot that carbamylated and citrullinated proteins are present in EMVs from RA patients. Moreover, surface marker phenotyping indicated that EMV treated-DCs exhibit increased expression of CD83 and CD86, as well as of CD83+ HLA-DR+ CD80+ CD86+ cells, indicating that the DCs are in a mature state. Furthermore, biochemical data demonstrated that EMVs from plasma of RA patients induce MAPK and NF-κB activation in DCs. EMVs from the plasma of RA patients were also able to stimulate DCs to produce IL-12, IL-1β and IL-10, inducing a proinflammatory phenotype.ConclusionsThese findings demonstrate that EMVs from RA patients promote DC activation in vitro, suggesting a potential mechanism by which RA microenvironment perpetuates inflammation through the modulation of DC function. These knowledges provide new insight in the role of EMVs in the pathogenesis of RA and their potential role as therapeutic targets.